Optimizing Internet flows over IEEE 802.11b wireless local area networks a performance-enhancing proxy based on forward error correction. - Munoz, L. (IEEE Communications magazine)
The success of the IP and its associated technologies has led to new challenges as we try to use it more widely in everyday communications. In particular, the drive toward wireless and highly heterogeneous infrastructures supporting IP services transparently and independent of the underlying physical layer is a challenge. In this context, this article focuses on introducing an implementation of a generic performance-enhancing proxy, called the wireless adaptation layer, and particularly its forward error control enhancement module. The error control module is a potentially important tool for achieving better UDP and TCP performance over the inherently unreliable wireless channels, and providing some adaptation for that. In order to assess the benefits and drawbacks of the selected design, we have also conducted some performance measurements over IEEE 802.11b WLANs